Deletion of CCK2Receptor in Mice Results in an Upregulation of the Endogenous Opioid System - Blandine Pommier; F. Beslot; Axelle Simon; Matthieu Pophillat; Toshimitsu Matsui; Valérie Daugé; Bernárd P. Roques; Florence Noble (2002)
Stimulation of the brain CCK2 receptor by the C-terminal octapeptide CCK8 of cholecystokinin (CCK) negatively modulates opioid responses. This suggests the existence of physiologically relevant interactions between endogenous CCK and opioid peptides, opening new perspectives particularly in the treatment of pain or drug addiction. CCK2 receptor-deficient mice were used to analyze the incidence of this gene invalidation on opioid system. Compared with wild-type mice, mutants exhibited the following: (1) a hypersensitivity to the locomotor activity induced by inhibitors of enkephalin catabolism or by morphine; (2) a spontaneous hyperalgesia to thermal nociceptive stimulus, which was reversed by previous administration of the NMDA antagonist MK-801 [(+)-5-methyl-10,11-dihydro-5H-dibenzo [a,d] cyclohepten-5,10-imine maleate], and a large reduction in analgesic effects of endogenous or exogenous opioids; and (3) a more severe withdrawal syndrome after chronic morphine treatment. As expected, stimulation of μ, δ, and D2 receptors on brain tissue of wild-type animals induced a dose-dependent decrease in adenylate cyclase activity, whereas a striking mirror effect was observed in mutants. All of these results suggest that the absence, in knock-out mice, of the negative feedback control on the opioid system, normally performed out by CCK2 receptor stimulation, results in an upregulation of this system. These biochemical and pharmacological results demonstrate the critical role played by CCK2receptors in opioid-dependent responses.